Proyecto para la creación de un complejo ecoturístico en la parroquia Canuto del cantón Chone - Ruales Alcívar, Janeth Carolina (2013)
The research aimed to design an ecotourism complex on the site of the parish's Juanita Canton Canute Chone. Were consulted bibliographic data from various authors to complete the theoretical framework of the project. We developed a methodological procedure which structured the phases and stages of research and ecotourism complex design, for which we conducted a market study which was characterized in the supply and demand through a diagnosis. The results of this assessment, showed that it is possible to build an ecotourism resort in the parish Canuto. To analyze the potential impacts on the environment caused by the implementation of the complex, was required an environmental study in the selected area for construction. Costs were also determined through a financial study. The results of these studies showed that it is possible to implement an ecotourism complex that has accommodation, food and recreation. The research showed that the implementation of this complex will allow the development of ecotourism in the parish Canuto, and therefore impact on economic improvement Juanita sector by increasing the influx of surplus value by local and foreign visitors.